2021
DOI: 10.1097/scs.0000000000007450
|View full text |Cite
|
Sign up to set email alerts
|

Globalization of The Journal of Craniofacial Surgery Over The Last Decade: A Continent, Country, and State Level Analysis

Abstract: Craniofacial surgery continues to be a rapidly evolving field, due in part to interdisciplinary collaboration that has allowed for sharing of knowledge and methodologies, which has expanded greatly due to online journals and publications. The Journal of Craniofacial Surgery (JCS) is a highly regarded journal that has attracted attention for its mission to increase diversity and global representation in manuscript submissions and research publications. The purpose of this study is to provide an objective measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The Journal of Craniofacial Surgery was the most popular journal among the Asian countries studied, namely, China, Turkey, South Korea, and Japan. According to a study by Liechty et al (2), Asia was the main contributor to this journal, producing 55.8% of its total publication in the 2010s. In addition, we noted 7 of the analyzed countries published most of their articles in journals specializing in craniofacial surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Journal of Craniofacial Surgery was the most popular journal among the Asian countries studied, namely, China, Turkey, South Korea, and Japan. According to a study by Liechty et al (2), Asia was the main contributor to this journal, producing 55.8% of its total publication in the 2010s. In addition, we noted 7 of the analyzed countries published most of their articles in journals specializing in craniofacial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, the quality of articles contributed by plastic surgeons to plastic surgery journals has significantly increased (1). There is considerable variation in the distribution of contributing countries to some prestigious plastic surgery journals (2,3). China has invested much in biomedical research and development (R&D), leading to developments in various surgical specialties in the past years (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained can provide an idea about the critical issues of the field and guide young researchers. 7 Liechty et al 6 recently evaluated and analyzed articles published in the Journal of Craniofacial Surgery between 2010 and 2019. After that, Bahs ¸i et al 27 assessed the first 25 most cited articles among the articles published between 1995 and 2020 in the Journal of Craniofacial Surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the number of articles published in the Journal of Craniofacial Surgery has mostly steadily increased since 1995 27 . Moreover, Liechty et al 6 reported that the articles published in the Journal of Craniofacial Surgery in the past decade were from 78 different countries. Besides, they stated that the Journal of Craniofacial Surgery has the most diverse representation of countries than other leading plastic and reconstructive journals 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Craniofacial surgery represents a diverse surgical subspecialty whose practitioners are responsible for evaluating and treating a myriad of conditions ranging from syndromic craniosynostoses to traumatic defects. As with other fields of medicine, there has been a substantial expansion of research in recent years 1,2. Traditionally, citation count has been utilized to parse influential papers, although significant criticism has been associated with this measure 3.…”
mentioning
confidence: 99%